Respiratory acidosis in adolescents with anorexia nervosa hospitalized for medical stabilization: A retrospective study - Kerem, Nogah C.; Riskin, Arieh; Averin, Elvira; Srugo, Isaac; Kugelman, Amir (The International journal of eating disorders, 2012)
Objective: To examine the effect of malnutrition due to anorexia nervosa (AN) on venous blood gases of adolescents with AN hospitalized for medical stabilization. Method: This retrospective study included 45 adolescents with recent onset (<1 year) AN diagnosed by DSM‐IV criteria and excluded subjects with a history of lung disease. Results: Mean (±SD) age at hospitalization was 15.0 ± 2.0 years; time from onset of symptoms was 6.8 ± 3.0 months; body mass index (BMI) was 15.2 ± 1.5 kg/m2; and minimal nocturnal heart rate (MNHR) was 39.8 ± 7.2 beats/min. On admission, pH was 7.32 ± 0.02, pCO2 was 53.8 ± 4.6 mm Hg, and HCO3 was 28.1 ± 2.1 mEq/l. Significant changes (p < .001) occurred during the relatively short hospitalization (9.7 ± 5.1days): venous pH increased, pCO2 decreased, HCO3 decreased, MNHR increased, and heart rate orthostasis decreased. Mild respiratory acidosis (pH < 7.35 and pCO2 > 45 mm Hg) was observed in 78% of the patients on admission and only in 35% at discharge (p = .0003). Positive correlations were found between % of weight loss and pCO2 on admission and between BMI on admission and the delta pCO2 during hospitalization. Discussion: Mild respiratory acidosis is common in adolescents with recently diagnosed AN, hospitalized for medical stabilization. Respiratory acidosis improves with bed rest and refeeding. The clinical significance of these findings should be further evaluated. © 2011 by Wiley Periodicals, Inc. (Int J Eat Disord 2012)